An assessment of site suitability for marina construction in Istanbul, Turkey, using GIS and AHP multicriteria decision analysis - Gumusay, Mustafa Umit; Koseoglu, Gokalp; Bakirman, Tolga (SPRINGER, 2016)
Marinas play a key role in sea transportation and tourism. The problem of an insufficient marina capacity has revealed in terms of sea traffic due to the demographic structure and increasing tourism potential of Istanbul which is the biggest metropolitan city of Turkey and has around 600-km-long coastline. Therefore, the study area is mainly focused on the Marmara Sea shoreline of Istanbul. Rather than traditional methods, a rapid and cost-effective solution which considers natural and urban environment conditions is essential to satisfy the need for a marina site selection. Thanks to the latest improvements in geographic information systems, it is convenient to perform location selection analysis of marinas taking advantages of geology, land use, demography and accessibility data sets. The goal of this study is to define the areas that are appropriate for building marinas, with the use of topographic and demographic data in a present shoreline applying analytical hierarchy process multicriteria decision-making method. In this study, erosion, landslide, tsunami, land use, geologically hazardous areas, transfer lines, sea traffic data, neighbourhood scale population, age patterns and house income data have been used. Analytical hierarchy process method is used to give a weight to each data set, and a grading system has been developed for the area selection of marinas. The result maps of the analysis that show study area as classified into four categories from good to not suitable are presented. It is possible to create a decision support system for upper scale plans that enable authorities to perform analysis accurately, cost and time effectively using the proposed methodology that integrates multiple data sets with different scales and types.
Keywords: GIS; Marina; Multicriteria decision-making; AHP; Coastal planning; HABITAT SUITABILITY; HIERARCHY PROCESS; RECLAIMED WATER; SUITABLE SITES; FUZZY-AHP; COASTAL; SELECTION; CHINA; MANAGEMENT; PROJECTS; Environmental Sciences & Ecology